Analisis Ketersediaan Ruang Terbuka Hijau Menggunakan Pendekatan Indeks Hijau-Biru Indonesia Di Kelurahan Tamalanrea - Tombe, Monica; Fuad Aziz, Muhammad; Budiharto, Tri; Jibran, Muh. Khalil (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study is to determine the availability of green open space in Tamalanrea Village and how the strategy to maximize green open space in Tamalanrea Village can be an input or reference for the government as a policy determinant in the development, private parties, social institutions, or communities that act as development implementation and for planners in terms of increasing development, especially in terms of providing green open space. This qualitative research uses data collection techniques using observation, interview, documentation, and literature study methods. The data obtained were then analyzed using the spatial approach, qualitative descriptive analysis, and Indonesian Green-Blue Index (IHBI) approach. The conclusion of this study is that the availability of green open space in Tamalanrea Village based on MINISTER OF ATR / BPN Number 14 of 2022 concerning the provision and utilization of green open space consisting of allotment areas or green open space zones, namely RT parks and green lanes, allotment areas or other zones, namely agricultural areas, green open spaces on plots, namely parcels in residential zones, parcels in office zones, and home yards, as well as blue open space areas, namely lakes whose availability needs to be maximized ecologically and socially based on MINISTER OF ATR / BPN Number 14 of 2022.